Profil Fitokimia dan Uji Toksisitas Daun Tumbuhan Aglaia Odorata dengan Metode Brine Shrimp Lethality Test - Mai Efdi; Ridho Sahary Adha; Adlis Santoni (Jurnal Kimia Unand, 2022)
Toxicity and phytochemistry assay have been conducted on extracts and fractions of Aglaia odorata leaves using brine shrimp lethality test. Aglaia odorata is one of the plants that are found in Indonesia. To investigate Aglaia odorata leaves potential as anticancer, air-dried and powdered leaves were extracted with n-hexane, ethyl acetat, and metanol by using maceration method. Extract of ethyl acetat showed the highest toxicity with LC50 value is 125.89 mg/L